Forgotten Origins, Occluded Meanings: Translation of Emotion Terms. (April 2017) - Wassmann, Claudia
The interdisciplinary field of emotion studies disregarded historical perspectives on translation and left out a substantial body of scientific research on feelings and emotions that was not published in English. Yet these texts were foundational in forging the scientific concept of emotion in experimental psychology in the 19th century. The current approach to emotion science overlooks that translation issues occurred between three languages, German, French, and English, as physiological psychologists at the time were reading each other in these languages all the while writing about the same topics in their respective language. Historical perspectives are important to clarify the ambiguities of emotion terms and include non-Anglophone frameworks into current transdisciplinary debates.